2015
DOI: 10.3892/or.2015.4479
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 sensitizes colorectal cancer to 5-fluorouracil through cell cycle arrest by inhibiting the PI3K/Akt/CDC2/survivin cascade

Abstract: Abstract. 5-Fluorouracil (5-FU), a cell cycle-specific antimetabolite, is one of the most commonly used chemotherapeutic agents for colorectal cancer (CRC). Yet, resistance to 5-FU-based chemotherapy is still an obstacle to the treatment of this malignancy. Mutation or loss of Smad4 in CRC is pivotal for chemoresistance. However, the mechanism by which Smad4 regulates the chemosensitivity of CRC remains unclear. In the present study, we investigated the role of Smad4 in the chemosensitivity of CRC to 5-FU, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Activation of PI3K/AKT signaling pathway in cancer results in increased cell survival, outgrowth and enhanced cell migration (25). Inhibition of its activation will downregulate expression of survivin, MMP1, 2, 3, 9, 12, 13 and MT1-MMP, thus, suppresses the proliferation, migration and invasion of cancer cells (26)(27)(28)(29)(30)(31). Our results showed that GRA treatment significantly suppresses the phosphorylation of PI3K and AKT in LoVo, SW620 and SW480 cells, and the phosphorylation of PI3K occurs as early as 2 h after GRA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PI3K/AKT signaling pathway in cancer results in increased cell survival, outgrowth and enhanced cell migration (25). Inhibition of its activation will downregulate expression of survivin, MMP1, 2, 3, 9, 12, 13 and MT1-MMP, thus, suppresses the proliferation, migration and invasion of cancer cells (26)(27)(28)(29)(30)(31). Our results showed that GRA treatment significantly suppresses the phosphorylation of PI3K and AKT in LoVo, SW620 and SW480 cells, and the phosphorylation of PI3K occurs as early as 2 h after GRA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin is also correlated with the poor prognosis of colorectal adenocarcinoma patients (13,(15)(16)(17)(18)(19). Survivin takes part in the cell apoptosis of gastric cancer cells (21,22), and is involved in cell cycle arrest in colorectal cancer (23). Increased apoptosis by a survivin inhibitor is considered as an effective treatment for colon cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of survivin induces mitochondrial-mediated apoptosis in gastric cancer cells (21,22). In addition, survivin is involved in the cell cycle arrest of colorectal cancer cells (23). Increased apoptosis by a survivin inhibitor is considered as an effective treatment for colon cancer (24).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that ectopic expression of SMAD4 induced apoptosis on SiHa cells (Lee et al, 2001), and reduced cervical cancer growth in nude mice (Klein-Scory et al, 2007), indicating a tumor suppressive role for SMAD4 in cervical cancer. Different groups have reported a positive correlation between SMAD4 expression and sensitivity towards cetuximab in head and neck squamous cell carcinoma (Cheng et al, 2015) as well as 5-fluorouracil in breast (Yu et al, 2013) and colorectal cancer (Papageorgis et al, 2011; Zhang et al, 2014; 2016). In this study, we showed that overexpression of SMAD4 in cervical cancer cells augmented anti-proliferative and apoptosis-inducing effects of ACA, indicating that SMAD4 plays a role in regulating response towards anti-cancer agents.…”
Section: Discussionmentioning
confidence: 99%